Derrida and the end of history - Sim, Stuart (Icon Books ; Totem Books ; In the U.S., distributed to the trade by National Book Network, 1999)
Derrida's critique of Fukuyama's claim that history "as we know it" has ended is highlighted as one of his most valuable contributions to the postmodern cultural debate. This book places Derrida's rejection of Fukuyama's claim within the context of a wider tradition of 'endist' thought.